Two-Dimensional Materials for Highly Efficient and Stable Perovskite Solar Cells - Shen, Xiangqian; Lin, Xuesong; Peng, Yong; Zhang, Yiqiang; Long, Fei; Han, Qifeng; Wang, Yanbo; Han, Liyuan (Nano-Micro Letters, 2024)
Perovskite solar cells (PSCs) offer low costs and high power conversion efficiency. However, the lack of long-term stability, primarily stemming from the interfacial defects and the susceptible metal electrodes, hinders their practical application. In the past few years, two-dimensional (2D) materials (e.g., graphene and its derivatives, transitional metal dichalcogenides, MXenes, and black phosphorus) have been identified as a promising solution to solving these problems because of their dangling bond-free surfaces, layer-dependent electronic band structures, tunable functional groups, and inherent compactness. Here, recent progress of 2D material toward efficient and stable PSCs is summarized, including its role as both interface materials and electrodes. We discuss their beneficial effects on perovskite growth, energy level alignment, defect passivation, as well as blocking external stimulus. In particular, the unique properties of 2D materials to form van der Waals heterojunction at the bottom interface are emphasized. Finally, perspectives on the further development of PSCs using 2D materials are provided, such as designing high-quality van der Waals heterojunction, enhancing the uniformity and coverage of 2D nanosheets, and developing new 2D materials-based electrodes. Highlights: 1 Recent progress on the applications of 2D materials in perovskite solar cells is discussed from the views of bottom interfaces, top interfaces, and electrodes. 2 The roles of van der Waals heterojunction in enhancing the performance of perovskite solar cells are highlighted. 3 The future directions and challenges in development of 2D materials-based perovskite solar cells are provided.